Protocol for peripheral parenteral nutrition management ready to use in surgical patients (2015)
Introduction: Patients undergoing elective surgery, require a comprehensive clinical treatment that tends to maintain or prevent deterioration of nutritional status and promote clinical outcomes, and in turn improve the safety of parenteral nutrition therapy through optimization of technology, as a option aimed at minimizing risk and lower operating costs in institutions providing health services. Aim: To review the literature in order to study the requirements and recommendations of peripheral parenteral nutritional support and/or complementary ready to use in people undergoing surgery. Methods: Data synthesis after reviewing the relevant literature, to allow the protocol design. The search was conducted in the following databases: PubMed, Medline, Embase and Science Direct. Conclusions: Peripheral parenteral nutrition is a ready to use alternative nutritional support that improves the contribution Protein-Energy and demonstrate improvements in patient safety, decrease costs and increase patient satisfaction. © 2015, Grupo Aula Medica S.A. All rights reserved.